Utilization ethanol extract of sappan wood as an alternative in escherichia coli staining - mamay, mamay (Institute Of Computer Science (IOCS), 2024)
In life, sappan wood is used as an ingredient in traditional drinks that has antioxidant, antimicrobial and has stable pigments. The content of red pigment, brazilin in sappan wood can be used as a dye. The purpose of this study was to determine the potential of sappan wood ethanol extract as an alternative to safranin in gram staining. Ethanol extract of sappan wood 6% was added with alum mordant to obtain a red pigment. The bacteria used Eschericia col, isolated from water. Staining using ethanol extract of sappan wood was carried out for 30 seconds, 3, 5 and 10 minutes. This stain was compared with safranin. The results showed that staining using sappan wood extract shows clarity of the visual field, shape and good color. Based on the results, the ethanol extract of sappan wood with mordant can be used as an alternative to safranin in the gram-staining.